Tackling network insecurity in Singapore - Teo, Alvin Guo Yang (2015)
This paper seeks to establish the relationship between online insecurity of critical networks in Singapore, also termed as network insecurity, and the maintenance of Singapore's national security and its competitive advantages. Accordingly the question of network insecurity is tackled and assessed according to available information on key civilian and military networks in Singapore. Qualitative analysis is used here and the main analytical approach adopted would be interdisciplinary. This paper draws as well as deviates from current literature on network insecurity and cyber vulnerabilities. It tries to assess the security of networks in civilian and military networks in Singapore based on a framework comprising of several drivers rarely discussed in academic literature such as legislation, enforcement and cyber literacy. It also explores the approaches taken to counter such online vulnerabilities, though mainly from a topdown approach with the government firmly taking the lead. It also explores scenario formulation of attacks by state and non-state actors on various networks in Singapore. Therefore I seek to argue that ultimately, Singapore faces a serious issue of insecurity of its networks, especially in the civilian network infrastructure as compared to the military.